Russia's Legal Policy Against Diaspora Marriages in Muslim Communities - Mesraini, Mesraini; Yunus, Nur Rohim (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This article discusses the politics of marriage law in the Russian Muslim diaspora. The Muslim community in Russia faces challenges in carrying out their marriage according to the principles of the Islamic religion amidst the legal regulations in force. This article analyzes the political development of marriage law in the Russian Muslim diaspora, including the recognition of Islamic marriage law, the settlement of legal conflicts between Islamic marriage and state law, and the role of Islamic organizations in safeguarding Muslim marriage rights. This article also presents case studies, examples of legal marriage practices in the Russian Muslim diaspora, and obstacles and solutions encountered in dealing with different legal regulations. This study uses normative research methods. Conceptual, literary and sociological approaches are used in normative or doctrinal research. Data analysis in this study used qualitative analysis methods. The results of the study state that there are political implications of the marriage law of the Russian Muslim diaspora, in addition to the challenges and opportunities in fulfilling the elements of the rights of the Muslim community in Russia. Therefore, it is expected to contribute to broadening the understanding of the politics of marriage law in the Russian Muslim diaspora and exploring issues related to Muslim marriage rights in the context of that country.